LOAN LOSS PROVISIONING BEHAVIOUR OF CYPRIOT BANKS: A STUDY FOR PROCYCLICALITY, INCOME SMOOTHING AND CAPITAL MANAGEMENT - Roussos, Angelos (2012)
This paper investigates the loan loss provisioning behaviours of Cypriot banks and how they are related to the business cycle, income smoothing and capital management. Overall, thirteen banks were selected for this study between the period 1997-2011, and both the random effects model and the Generalized Method of Moments (GMM) estimator were used to conduct the analysis. In a brief summary of my findings, Cypriot banks seem to give a lot more weight on their own internal actions and characteristics when deciding on their provisioning amounts, rather than the external economic factors. Results showed banks’ provisions are countercyclical to the business cycle but due to the fact that banks do not participate in income smoothing practices and because earnings have a bigger role in provisioning decisions, those countercyclical tendencies due to GDP growth are overshadowed. There are also signs of capital management, albeit at terribly small amounts. The lagged dependent variable and the impaired loans variable are also significant, indicating that banks adjust their provisions according to the previous year’s levels, and that they also respond to realized credit risk.